Isolasi dan Identifikasi Mikroba Amilolitik Selama Fermentasi Spontan Pisang Kepok (Musa paradisiaca) - Yasir, Khaerunnisa; Sukainah, Andi; Mustarin, Amirah (Agricultural Technology Education Study Program, 2024)
This research is an experimental study that aims to determine the results of microbial isolation during spontaneous fermentation of kepok bananas and to determine the results of amylolytic activity tests during spontaneous fermentation of kepok bananas. The number of microbes that were isolated and identified during spontaneous fermentation of banana kepok were 21 isolates, there were 15 isolates which of were yeast types and 6 isolates from bacteria. Microbes with yeast types have 3 shapes, namely round, oval, and cylindrical. The types of bacteria produced were 4 isolates with Gram-positive characteristics, 2 isolates that produced endospores, and 2 isolates with positive catalase. The test results of the microbial amylolytic activity of yeast and bacterial isolates obtained during the spontaneous fermentation of kepok bananas showed 16 isolates capable of hydrolyzing starch, 14 isolates from yeast, and 2 isolates from bacteria. Of the 16 isolates, AT3I5, AT9I3, and AT9I1 had the ability to hydrolyze starch at 11.2 mm, 10 mm, and 9.4 mm, respectively. It was recommended for further testing.